2020
DOI: 10.3390/jcm9092828
|View full text |Cite
|
Sign up to set email alerts
|

Pain Trajectories in Knee Osteoarthritis—A Systematic Review and Best Evidence Synthesis on Pain Predictors

Abstract: Different profiles of pain progression have been reported in patients with knee osteoarthritis (OA), but the determinants of this heterogeneity are still to be sought. The aim of this systematic review was to analyze all studies providing information about knee OA pain trajectories to delineate, according to patients’ characteristics, an evidence-based evolution pattern of this disabling disease, which is key for a more personalized and effective management of knee OA. A literature search was performed on PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“… 11 Another applicable method is the pain trajectories evaluation, which aims, through a repetitive assessment of the patient’s pain level, to better characterize and evaluate different profiles of pain progression rather than with less reliable 1-time evaluations. 32 , 37 Similarly, the MCID and the PASS are important tools for documenting the magnitude of patient improvement and well-being after treatment, allowing a more patient-focused outcome than statistics can provide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Another applicable method is the pain trajectories evaluation, which aims, through a repetitive assessment of the patient’s pain level, to better characterize and evaluate different profiles of pain progression rather than with less reliable 1-time evaluations. 32 , 37 Similarly, the MCID and the PASS are important tools for documenting the magnitude of patient improvement and well-being after treatment, allowing a more patient-focused outcome than statistics can provide.…”
Section: Discussionmentioning
confidence: 99%
“…rather than with less reliable 1-time evaluations. 32,37 Similarly, the MCID and the PASS are important tools for documenting the magnitude of patient improvement and well-being after treatment, allowing a more patientfocused outcome than statistics can provide.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study was the lack of a control group. Therefore, we could not rule out the presence of a placebo effect, which can be crucial for pain symptoms [ 5 , 25 ]. Indeed, the presence of a control group is essential to confirm the efficacy of the described treatment versus arthroscopy alone, and will be a subject of our next study; moreover, further investigations will compare this new treatment with standard options such as hyaluronic acid or PRP injections.…”
Section: Discussionmentioning
confidence: 99%
“…Given that OA-related pain can be experienced as persistent or intermittent, with ongoing fluctuations in intensity, longitudinal studies using annual or bi-annual assessments may not fully capture clinical pain variability [ 18 ], and daily assessments place undue burden on patients. Therefore, identification of pain trajectories in knee OA based upon quarterly assessments may prove optimal by balancing the benefit to burden ratio [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite evidence for associations between sociodemographic factors and pain trajectories [ 18 , 34 ], little is known about the relationship between ethnicity/race and pain progression in knee OA. Previous research has demonstrated considerable health disparities in knee OA, with African Americans/non-Hispanic Blacks (NHBs) reporting greater overall levels of clinical pain and physical disability [ 21 , 35 – 37 ], and experimental pain sensitivity [ 10 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%